Avaliação do conhecimento dos pediatras e neonatologistas com atuação na unidade neonatal da Fundação Santa Casa de Misericórdia do Pará sobre retinopatia da prematuridade - CARVALHO, Luiz Claudio Portilho de (2022)
Objectives: To assess the degree of knowledge of pediatricians and/or neonatologist with experience in the neonatal unit of Santa Casa de Misericórdia do Pará (FSCMPA) on retinopathy of prematurity regarding the diagnosis and management. Methods: This study is a cross-sectional study, prospective and analytical study which applied a questionnaire to pediatricians and/or neonatologists working in neonatal unit of FSCMPA knowledge about the diagnostic test, screening for gestational age and weight at birth, which most serious complication and weeks after birth is ideal for the examination of retinopathy of prematurity. The statistical tests were done by the software BioEstat 5. Results: There were 38 doctors, the average age of them was 42 years. Minimum age 30 maximum of 60 years, 7.89% males and 92.11% females; 34.21% 65.79% were pediatricians and neonatologists, the average performance in the neonatal unit was FSCMPA 11.5 years, all the respondents reported having knowledge about what is retinopathy of prematurity; in relation to the diagnostic examination 89.47% responded that the mapping of the retina, also 89.47% responded that the primary retinal complications; 60 , 53% answered that request the examination only in the diagnosis of retinopathy of prematurity FSCMPA, while 36.84% of the newborns request in FSCMPA and outside this, 100% of those interviewed were unanimous about the obligation of endoscopic diagnosis of retinopathy of prematurity in nurseries; in relation to screening from that weight would be important to perform the diagnostic test, 42.10% in ≤ 2,000 g; regarding screening and diagnostic gestational age, 60.53% answered ≤ 37 weeks, about which week after birth is indicated the exam, 86.84% responded in the fourth week, taking into account weight and gestational age together 31.57% got both indications for screening, only 10.53% knew the weight, 28.95% got only gestational age 28.95% and missed the two screening parameters; Conclusion: The study proved relevant by virtue of showing that pediatricians and / or neonatologists working in neonatal unit FSCMPA not have adequate knowledge of triage is an RN has an opportunity to present retinopathy of prematurity or the guidelines established by the institution are not strictly followed.